Synthesis and characterization of aluminum titanium carbonitride TiAlCN via mechanical alloying (2010)
This study presents synthesis of titanium aluminum carbonitrides alloy (TiAlCN) by mechanical alloying in Attritor ball mill from elemental powders of titanium, aluminum and graphite in nitrogen atmosphere. TiAlCN was characterized by SEM, XRD, DSC and FTIR techniques. XRD showed presence of titanium aluminum nitride, aluminum nitride, titanium carbide and titanium aluminum carbon nitride, while SEM showed existence of micro and nano particles with high agglomeration. Energy-dispersive spectroscopy (EDS) analysis shows a homogeneous distribution of elements, and mapping analysis from X-rays confirms distribution of elements. Introduction Development of Ti-Al-N ternary alloy gives an increase in hardness and oxidation resistance in comparison with binary alloy TiN 1 . Quaternary alloys type, titanium aluminum carbonitride titanium (Ti-Al-N-C) has been produced by pulsed laser deposition technique 2-3 , magnetron sputtering technique 6 , and chemical depositions techniques 4 . Titanium aluminum carbonitrides alloy (TiAlCN) hard coating shows high wear and erosion resistance, under high cutting velocity and without lubrication 6 . This study presents synthesis by mechanical alloying and characterization of powder alloy TiAlCN as target to obtain hard coatings. Experimental Section TiAlCN powder (Ti, 55.1; Al, 31.0; and C, 13.9%) was obtained by mechanical alloying in a ball milling atritor of vertical impeller 6 . A stainless steel vial and various Cr steel balls (diam, 6-8 mm) were used. Elemental powder contained: pure Ti (particle size, 150 µm), 99.7 wt%; Al (particle size, < 200 µm), 99.95 wt%; and C (particle size, <45 µm), 99.99 wt%. Mill container air was evacuated using a vacuum pump and then filled with nitrogen gas. Mass balls and powder ratio was 70:1, with 500 rpm constant rotational velocity for 140 h.